(untitled) (Confluenţe Bibliologice, 2019)
The article highlights the most important achievements of the USARB Scientiﬁc Library in 2018. The Library’s participation in the Projects has facilitated new knowledge and experiences, documentary visits in libraries in European countries, training workshops, webinars, promoted by international experts ,technical equipment worth more than 500 000 lei, international visibility in a virtual and physical way. The library was included in the Open World program, supported by the US Congress. The development of a modern system of information resources, services and educational products relevant to each specialty, specialization, doctorate and postdoctoral discipline continued.